Improving the production of baculovirus expression vector by overexpression of IE0/IE1 through tandem promoter - Sijun He; Weining Li; Ruirui Zhang; Hao Nan; Wangcheng Song; Xiaodong Xu (PLoS ONE, 2025)
The baculovirus expression vector system, known for its protein production in insect cells and has been criticized for its relatively low expression capacity. IE0/IE1, acknowledged vital early regulators of baculovirus, are indispensable for the virus proliferation and regulate the expression of various genes within the virus. Prior research has reported a substantial rise in exogenous gene expression upon overexpression of IE01. In this study, to mitigate the risk of generating defective viruses due to homologous recombination, we introduced an additional promoter in vivo within the viral genome, thus overexpressing IE0/IE1. The research outcomes demonstrate that the expression of exogenous proteins is notably enhanced without the homologous regions sequence for enhancement. In parallel, they still indicate that the upregulation of IE0/IE1 not only boosts viral titers but also enhances apoptosis within cellular populations. In sum, we successfully constructed a novel baculovirus expression vector that significantly enhances the expression of exogenous genes, presenting a new perspective for optimizing the baculovirus expression vector system.